2012
DOI: 10.1515/epoly.2012.12.1.1023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cross-linked comb-type polysiloxane for polymer electrolyte membranes

Abstract: Hydrosilylation reaction of 2.4.6.8-tetrahydro-2.4.6.8-tetramethylcyclotetrasiloxane with allyl acetoacetate and vinyltriethoxysilane at 1:3:1 ratio of initial compounds in the presence of Karstedt's catalyst (Pt 2 [(VinSiMe 2 ) 2 O] 3 ), platinum hydrochloric acid (0.1 M solution in THF) and platinum on the carbon have been studied and D 4 R,R' type methylorganocyclotetrasiloxane has been obtained. Ring-opening co-polymerization reactions of methylorganocyclotetrasiloxane and hexamethyldisiloxane, in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Immobilization of TPC and calmoduline in the polyvinyl alcohol functional polymer: TPC and exogenous calmodulin 0.2-0.1 mg/ ml are added to the aqueous solution of the polyvinyl alcohol polymer. After mixing well, it is poured into the Teflon frame and after 48 hours, 50 μm thick and 1.5 cm diameter films are obtained, in which the active substance is immobilized [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…Immobilization of TPC and calmoduline in the polyvinyl alcohol functional polymer: TPC and exogenous calmodulin 0.2-0.1 mg/ ml are added to the aqueous solution of the polyvinyl alcohol polymer. After mixing well, it is poured into the Teflon frame and after 48 hours, 50 μm thick and 1.5 cm diameter films are obtained, in which the active substance is immobilized [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…By anionic ROP and further cross-linking of Si-O eightmembered rings with side-chain-modified PEO segments, a filmformable electrolyte was prepared by Lee et al Surprisingly, the room-temperature ionic conductivity of the electrolyte could exceed 1 × 10 −5 S cm −1 . [157] Abadie et al reported a similar work, [158] but the conductivity test alone was not sufficient to demonstrate the utility of the electrolyte. Xue Group synthesized a three-block polymer by anionic ROP and further crosslinked to obtain a SPE.…”
Section: Hexagonal Ring and Other Ringsmentioning
confidence: 99%
“…[ 157 ] Abadie et al. reported a similar work, [ 158 ] but the conductivity test alone was not sufficient to demonstrate the utility of the electrolyte. Xue Group synthesized a three‐block polymer by anionic ROP and further crosslinked to obtain a SPE.…”
Section: Current Progress Of Spes Based On Rop: From Ring Structuresmentioning
confidence: 99%
“…26 Hydrosilylation reactions focused on the modification of DH 4 with two different substrates (olefin or alkyne) leading to products with different content of the groups DSP 3 , DS 2 P 2 or DS 3 P are a more challenging task, definitely less frequently described in the scientific journals, and mainly disclosed in the patent literature. [52][53][54][55][56][57][58] Nevertheless, it must be noted that the distribution of both groups coming from two starting materials in the structures of synthesized products is often random. Moreover, detailed characterization of these compounds by NMR methods has not been provided in the majority of these reports.…”
Section: Introductionmentioning
confidence: 99%